Extreme evolutionary shifts in developmental timing establish the miniature Danionella as a novel model in the neurosciences. Issue 4 (27th December 2020) - Conway, Kevin W.; M. Kubicek, Kole; Britz, Ralf
Abstract: Background: Species of Danionella rank among the smallest of all vertebrates and their miniature size is correlated with an extreme case of progenesis, resulting in tiny, transparent sexually mature individuals. Progenesis has affected the entire skeleton of Danionella, in which 60 skeletal elements are absent, including some of the skull roofing bones. This lack of a skull roof combined with the presence of a fully formed hearing and sound producing apparatus has led to Danionella being used as an important model for neurophysiological studies. Results: Using both rank based and PGi analyses we investigate sequence heterochrony in the development of the skeleton of Danionella dracula and close relatives. Extreme heterochronic shifts affect the appearance of bony elements in Danionella dracula . This includes a delay in the appearance of most chondral skull bones, and a reduction or loss of dermal bones that would otherwise form the skull roof. In contrast, formation of the anterior region of the vertebral column, including the functionally important elements of the Weberian apparatus, is greatly accelerated. Conclusions: Here we show that the anatomical conditions that favor Danionella for brain research are the result of extreme heterochronic shifts that have acted differentially across the skeleton. Key Findings: We conduct the first study of skeletal development in Danionella, an important emerging model in the neurosciences. In comparison to the zebrafish, 60 skeletal elements are absent in Danionella, including some of the skull roofing bones, the result of an extreme case of organism‐wide progenesis. The skeleton of the Weberian apparatus, an important sound reception device in otophysan fishes, exhibits an astonishingly precocious development in Danionella compared to zebrafish. The anatomical conditions that favor Danionella for brain research are the result of extreme heterochronic shifts that have acted differentially across the skeleton.